2016
DOI: 10.1007/978-1-4939-3816-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Drug Delivery in Neurotrauma

Abstract: The central nervous system (CNS) is protected by blood-brain barrier (BBB) and blood-cerebrospinal-fluid (CSF) barrier that limit toxic agents and most molecules from penetrating the brain and spinal cord. However, these barriers also prevent most pharmaceuticals from entering into the CNS. Drug delivery to the CNS following neurotrauma is complicated. Although studies have shown BBB permeability increases in various TBI models, it remains as the key mitigating factor for delivering drugs into the CNS. The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To resolve this issue, we administrated the mice with ABPPk via intranasal infusion. Previous studies have shown that intranasal infusion is an effective strategy for delivering drugs into the brain (Deng‐Bryant et al, ; Zhang et al, ). Mice were pretreated with ABPPk and then subjected to MPTP injection for seven consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…To resolve this issue, we administrated the mice with ABPPk via intranasal infusion. Previous studies have shown that intranasal infusion is an effective strategy for delivering drugs into the brain (Deng‐Bryant et al, ; Zhang et al, ). Mice were pretreated with ABPPk and then subjected to MPTP injection for seven consecutive days.…”
Section: Discussionmentioning
confidence: 99%
“…Acute intervention of oxidative stress processes could limit the negative effects of secondary injury mechanisms on TBI outcome. A challenge to TBI treatment, and the treatment of any central nervous system (CNS) disorder, is drug delivery to and across the BBB 21 . Notably, the endothelial cell layer that constitutes the luminal most component of the BBB represents an important therapeutic target in conditions involving oxidative stress and inflammation, such as TBI 22, 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Although many possible drug treatments with specific cell-based mechanisms of actions have been identified to promote neural repair and alleviate chronic pain, often only a small amount of drug is actually delivered to the disease site . The effectiveness of such treatments is compromised due to poor pharmacokinetic profiles, substantial off-target toxicity, and limitations with the administration route. Using chronic pain as an example, current therapeutics often rely on passive targeting, in which enhanced permeability at the injury site and spinal cord allow for extravasation of drugs into the CNS. , Yet, those agents are rapidly cleared from the blood and are not sufficiently delivered to the spinal cord where nociceptive processing occurs. Many chronic pain treatments in both human and animal studies have sought to improve efficacy by delivering therapies using intrathecal drug delivery systems. ,, Intrathecal drug delivery systems administer drugs directly into the spinal canal allowing direct access to cerebrospinal fluid, which improves on-target delivery as well as lowers the effective dose of drug needed. , However, such delivery systems, including intrathecal injections, are highly invasive and can result in complications like bleeding and infection .…”
Section: Multiscale Treatment Strategies For Neural Injurymentioning
confidence: 98%